The Influence of Competency, Job Placement, Work Discipline, And Workload on The Work Effectiveness of Bank Sumsel Babel Employees, Tebing Tinggi Branch, Empat Lawang Regency - Lisdalia; Nisma Aprini; Delvina Yulanda (PT. Altaf Publishing Corp, 2026)
This study aims to determine and analyze the influence of competency, job placement, work discipline, and workload, individually and collectively, on the work effectiveness of employees at Bank Sumsel Babel, Tebing Tinggi Branch, Empat Lawang Regency. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial tests, simultaneous tests, and coefficients of determination. The results showed that competency significantly influenced the work effectiveness of employees at Bank Sumsel Babel, Tebing Tinggi Branch, Empat Lawang Regency. Job placement significantly influenced the work effectiveness of employees at Bank Sumsel Babel, Tebing Tinggi Branch, Empat Lawang Regency. Work discipline and workload significantly influenced the work effectiveness of employees at Bank Sumsel Babel, Tebing Tinggi Branch, Empat Lawang Regency. Workload significantly influenced the work effectiveness of employees at Bank Sumsel Babel, Tebing Tinggi Branch, Empat Lawang Regency. Competence, job placement, work discipline, and workload have a significant joint influence on the work effectiveness of employees at Bank Sumsel Babel, Tebing Tinggi Branch, Empat Lawang Regency.